PENGARUH DAYA TARIK VIDEO STORYTELLING MARKETING DAN DAYA TARIK PACKAGING TERHADAP PERSEPSI MEREK HMNS PERFUMERY - Adam Gilang Ditsani; Nurist Surayya Ulfa; Sunarto Sunarto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
The role of brand in shaping consumer behavior within the perfume product category is widely acknowledged. However, the case of HMNS presents an intriguing anomaly as it exhibits high buying behavior in the e-marketplace, while its brand image position remains comparatively low. In an effort to enhance its brand image, HMNS employs video storytelling marketing and strategic packaging. This study aims to investigate the impact of the attractiveness of video storytelling marketing and packaging on the perception of the HMNS Perfumery brand, utilizing the Antecedent-Attribution theory as the theoretical framework. The study focuses on the population of HMNS social media followers, employing a non-probability sampling technique to gather responses from 50 individuals, encompassing both men and women aged 17-34 years who possess knowledge of Ambar Janma's products and have engaged with HMNS storytelling video content. The results of the hypothesis testing, conducted through multiple linear regression analysis, surprisingly indicate that neither the attractiveness of storytelling marketing nor the attractiveness of packaging significantly influence the perception of the HMNS Perfumery brand. These findings highlight the need for further exploration to understand the underlying factors contributing to the brand's low image position despite its strong buying behavior in the e-marketplace.